Gebrauchstauglichkeit digitaler Lesemedien - Veronika Geis (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2014)
– Applications on smart phones and tablets are in daily use by almost everybody. But how can developers guarantee an intuitive usage? What considerations are necessary to make the application user friendly? Which original new ideas need to be incorporated during the development of the Apps? This paper sketches the qualitative empirical research method of Usability test-ing, and applies it. It is engaged with DIN standards, laws and guidelines con-cerned with the theme »Usability in Mobile Internet«. Using a scheme based on these basic principles, three epaper Apps running on a third generation ipad were compared for their usability. The main focus of attention is the navigation: which of the tested concepts do offer the simplest logical and most intuitive solution for the end user? The three Apps chosen (Nürnberger Nachrichten, Süddeutsche Zeitung & Spiegel) were thereupon tested for their strengths and weaknesses. Finally, the results were used to make recommendations how the usability of epaper Apps could be improved.
urn:nbn:de:bvb:29-opus4-48795
Keywords: 650; App; Digitale Lesemedien; Gebrauchstauglichkeit; Publishing Industry; Usability; Digitale Medien; Benutzerfreundlichkeit; Deutschland